2015
DOI: 10.1021/acs.jpcc.5b08612
|View full text |Cite
|
Sign up to set email alerts
|

Energy Transfer Pathways in a Quantum Dot-Based Concentric FRET Configuration

Abstract: The unique optical properties of semiconductor quantum dots (QDs) are highly advantageous for biological imaging and analysis, particularly when combined with Forster resonance energy transfer (FRET). A recent innovation in this area has been concentric FRET (cFRET), wherein QDs are assembled with multiple copies of two different types of fluorescent label. Although multifunctional biological probes have been developed utilizing cFRET, a detailed photophysical analysis of cFRET has not been undertaken, and ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(56 citation statements)
references
References 62 publications
4
49
0
1
Order By: Relevance
“…The A555 PL is directly quenched by increasing A555-to-A647 FRET, and indirectly quenched through a reduction in the efficiency of QD-to-A555 FRET with increasingly competitive and efficient QD-to-A647 FRET. 537 Resolution of A555-to-A647 FRET requires either a correction for this competitive effect, or direct excitation of the A555 without excitation of the QD. 537 Experiments have shown that the A555-to-A647 E FRET depends strongly on N A647 , but its dependence on N A555 appears to be much smaller and is still unclear in its details.…”
Section: Aptamermentioning
confidence: 99%
“…The A555 PL is directly quenched by increasing A555-to-A647 FRET, and indirectly quenched through a reduction in the efficiency of QD-to-A555 FRET with increasingly competitive and efficient QD-to-A647 FRET. 537 Resolution of A555-to-A647 FRET requires either a correction for this competitive effect, or direct excitation of the A555 without excitation of the QD. 537 Experiments have shown that the A555-to-A647 E FRET depends strongly on N A647 , but its dependence on N A555 appears to be much smaller and is still unclear in its details.…”
Section: Aptamermentioning
confidence: 99%
“…184,185 Case 4 has largely been explored in university and other research institutions to construct portable clinical analyzers. [513][514][515][516][517][518][519][520][521][522][523][524][525][526][527][528][529] The fluorescence and colorimetric test reagents for clinical assays and analyses are well-known and widely available. In principle, therefore, interfacing microfluidics and a wavelength-selective device to a smartphone camera, with appropriate software, produces a mobile clinical analyzer with built-in communications abilities.…”
Section: Smartphone Spectroscopymentioning
confidence: 99%
“…This concentric relay design (cFRET) was used for multiplexed protease sensing [34]. While the attachment schemes for these systems are relatively simple, analysis can become difficult because the dyes can interact with each other as well as the quantum dot [28,193]. In 2017, a three-acceptor cFRET system was demonstrated by attaching three different enzyme cleavable peptides labeled with three discrete dyes to a QD donor [28].…”
Section: Multiplexed Sensingmentioning
confidence: 99%